Determination of heat transfer coefficient between casting and the modul - Jojin, Siniša; Kovač, Risto (Journal of Production Engineering, 1989)
In this paper, the interfacial heat transfer coefficient between the casting and the mold is described and determined. The determination of the interfacial heat transfer coefficient is based on temperature measurements within media on both sides of the interface. The results, determined from experimental measurements, present the values of the interfacial heat transfer coefficient as functions of time during the solidification of aluminum-based alloys.